Ralph S. Mouse - Cleary, Beverly; Zelinsky, Paul O. (New York : W. Morrow, 1982)
Presents the further adventures of a motorcycle-riding mouse who goes to school and becomes the instigator of an investigation of rodents and the peacemaker for two lonely boys.
Keywords: Mice -- Fiction; Juvenile fiction